2015
DOI: 10.1620/tjem.235.193
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life and Care Dependency among Elderly Hospital Patients: An International Comparison

Abstract: Many countries in Europe and the world have to cope with an aging population. Although health policy in many countries aims at increasing disability-free life expectancy, elderly patients represent a significant proportion of all patients admitted to different hospital departments. The aim of the research was to investigate the relationship between health-related quality of life (HRQOL) and the care dependency status among elderly hospital patients. In 2012, a descriptive survey was administered to a convenien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 22 publications
1
17
0
3
Order By: Relevance
“…[37] The quality of the CDS is similar to that of the Barthel Index, an appropriate instrument for assessing changes in care recipients over time. [38] Therefore, it is now used internationally [39] and has been adapted accordingly. [40][41][42] Since there is no clear definition of the social participation of residents, [43] it was analogous to Gilmour's [44] and described as daily physical activities, activities in contact with family or friendships, and recreational activities involving other people.…”
Section: Methodsmentioning
confidence: 99%
“…[37] The quality of the CDS is similar to that of the Barthel Index, an appropriate instrument for assessing changes in care recipients over time. [38] Therefore, it is now used internationally [39] and has been adapted accordingly. [40][41][42] Since there is no clear definition of the social participation of residents, [43] it was analogous to Gilmour's [44] and described as daily physical activities, activities in contact with family or friendships, and recreational activities involving other people.…”
Section: Methodsmentioning
confidence: 99%
“…The CDS is a tool for assessing the care dependency status of institutionalized patients, 16 and the Japanese version was developed by Suzuki. 17 The instrument comprises 15 care dependency items, each of which has an item description, and five care dependency criteria.…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…This can certainly diminish one's autonomy and the ability to be in control of one's life. 34 Finally, all the subgroups rated anxiety and as the aspect which was least burdensome. The dependent group rated attachment as the functioning with which they had the least trouble achieving, while the semi-dependent and independent groups rated control as functioning with which they had the least trouble achieving.…”
Section: Discussionmentioning
confidence: 97%
“…33 All these factors taken together might impact on the ability of the dependent group to be in control of their lives and to be self-sufficient. 34 The semi-dependent and independent groups are possibly concerned about the status of the health and finances since both groups reported that security, which includes monetary concerns and health, are affected considerably. Furthermore, literature suggests that impairment in leisure activities is related to "lower levels of symptom management and less active coping behaviour".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation